Medieval and Renaissance series. - Southeastern Institute of Medieval and Renaissance Studies (Chapel Hill University of North Carolina Press, 1966)
Irregular
Issued by the Southeastern Institute of Medieval and Renaissance Studies.
Keywords: Renaissance; Middle Ages